2020
DOI: 10.1142/s2424835520500010
|View full text |Cite
|
Sign up to set email alerts
|

Osteosynthesis of Postosteomyelitic Forearm Defects in Children Using a Modified Bone Grafting Technique: The Fibular Intramedullary Bridging Bone and Additional Grafting (FIBBAG)

Abstract: Background: There are many options to treat post osteomyelitic gaps in forearm bones. We report a pediatric series with postosteomyelitic forearm segmental defects reconstructed with fibular only graft: the non vascular fibular intramedullary bridging bone and additional grafting (FIBBAG) and the results thereof. Methods: Outcomes in 8 patients treated with fibular strut and overlay matchstick grafts were retrospectively assessed. The clinical results were expressed as forearm shortening, range of motion at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…According to the 2 systematic reviews by Siebelt et al5 and Solla et al,22 VFBG has the best clinical outcome in congenital forearm pseudoarthrosis. This shift toward vascularized grafting techniques in treating segmental gaps in long bones has also emerged in other situations, such as nonunions of infantile osteomyelitis in the forearm, another rare condition present in our second patient 25,26. Nonunion in OI is not uncommon.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…According to the 2 systematic reviews by Siebelt et al5 and Solla et al,22 VFBG has the best clinical outcome in congenital forearm pseudoarthrosis. This shift toward vascularized grafting techniques in treating segmental gaps in long bones has also emerged in other situations, such as nonunions of infantile osteomyelitis in the forearm, another rare condition present in our second patient 25,26. Nonunion in OI is not uncommon.…”
Section: Discussionmentioning
confidence: 76%
“…This shift toward vascularized grafting techniques in treating segmental gaps in long bones has also emerged in other situations, such as nonunions of infantile osteomyelitis in the forearm, another rare condition present in our second patient. 25,26 Nonunion in OI is not uncommon. The treatment of this nonunion is sometimes challenging, mostly when the nonunion has occurred spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…The combined tibial and fibular harvesting as described in our series, although being a known procedure, has scantly been elucidated in literature [5–7]. Our series on such 16 dual harvests showed that tibial healing proceeded unhindered being an incomplete window-type resection (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…The combined harvests, however, sum up as a major surgical procedure and require postoperative immobilization in a cast [5]. Postprocedure, the clinician’s focus is largely restricted to primary site outcome [6,7]. The overall impact of harvests on donor legs largely remains undocumented and therefore, formed the basis of the present research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation